Incorporating Individual Teachings (aka Individual Contact Teaching Methods) into a Sustainable Landscaping Extension Plan of Work and Report of Accomplishments - Laura Sanagorski (EDIS)
Many horticultural Extension professionals conduct numerous consulting phone calls, send e-mails, visit offices, conduct research, and visit landscapes to solve horticultural problems and concerns. Although many Extension faculty members are initially unaware that they are educating clients when providing these services, these activities should be considered major educational methods. The activities should also be planned by Extension faculty and reported in an Extension plan of work and in their annual report of accomplishments. When planned thoughtfully, communicated clearly, and evaluated appropriately, these methods of individual contact teaching can become a substantial part of an Extension program. This 4-page fact sheet was written by Laura Sanagorski, and published by the UF Department of Agricultural Education and Communication, November 2013. http://edis.ifas.ufl.edu/wc157